Hospital visiting policies in the time of coronavirus disease 2019: A nationwide website survey in Taiwan - Liu, Ya-An (J Chin Med Assoc, 2020)
Coronavirus disease 2019 (COVID-19), a novel infectious coronavirus disease, has become a worldwide pandemic. Infection control precautions for hospital visitors are needed to avoid cluster outbreaks, so this study investigated the visiting policies of all the hospitals in Taiwan in the time of COVID-19. METHODS: From March 15, 2020, to March 18, 2020, we searched the official websites of all 472 National Health Insurance–contracted hospitals to determine their visiting policies. For those hospitals that had posted new visiting policies and still allowed visits to ordinary wards, we recorded the relevant details shown on their websites, including the number of visitors allowed at one time, the number of visiting slots per day, the total visiting hours per day, and the rules provided to visitors before visiting. RESULTS: During the study period, 276 (58.5%) hospitals had posted new visiting policies on their websites, with higher proportions of academic medical centers (92.0%, 23/25) and metropolitan hospitals (91.5%, 75/82) than local community hospitals (48.8%, 178/365) doing so. Visits to ordinary wards were forbidden in 83 hospitals among those. Among the 193 hospitals that had new visiting policies and still allowed visits to ordinary wards, 73.1% (n = 141) restricted visitors to two at a time and 54.9% (n = 106) restricted visits to two visiting slots per day. Furthermore, history taking regarding travel, occupation, contacts, and cluster information was mentioned by 82.4% (n = 159) of these 193 hospitals, body temperature monitoring by 78.2% (n = 151), hand hygiene by 63.2% (n = 122), and identity checks by 51.8% (n = 100). CONCLUSION: In the time of COVID-19 covered by this study, about three-fifths of the hospitals in Taiwan had posted their visiting policies for ordinary wards on their websites. Furthermore, the thoroughness with which such visiting policies have been enforced also requires investigation.